Evaluating the impact of depression screening in general hospitals: a pilot study of patient reported outcomes of quality of life, functioning, and psychiatric symptom severity - IsHak, Waguih; Lopez, Enrique; Steiner, Alexander; Kharazi, Payam; Cedillo, Paula; Nimmer, Marcia; Bellete, Nardos; Benji, Ariella; Berberyan, Robert; Smith, Kimberly; Naghdechi, Lancer; Yahia Jaffer, Karim; et al. (International Journal of Medicine, 2016)
Background: Depression is common among patients with medical co-morbidities and has an adverse impact on wide ranging health outcomes. Depression is particularly prevalent in general hospital settings, where it has been linked to worse course of illness and higher rates of hospital readmission. While depression screening has been established as a best practice in outpatient settings, far less is known about the utility of screening for depression in inpatient medical settings.Aims: To determine whether screening for depression in a tertiary care medical hospital produces reliable and valid results. To identify obstacles and success factors that impact utility of depression screening. To evaluate the relationship between depression screening scores and patient-centered outcomes such as: functioning and quality of life.Method: Participants were 30 patients who were admitted to a tertiary care medical hospital, had a depression screening assessment completed by nursing on admission, and for whom a psychiatry consultation was requested. Patient responses to several measures were recorded and compared to PHQ screening on admission.Results: Depressed patients had significantly worse scores compared to non-depressed patients on the PHQ, WHO-5, PROMIS scores (global health, global mental health, physical functioning, anxiety, and fatigue), and Charleston Comorbidity Index (all p values < .05). Correlational analyses provided the strength of the relationships for each measures test-retest reliability.Conclusions: Findings support the clinical utility of screening for depression during inpatient hospital admissions. Assessing QOL, functioning, and psychiatric symptoms can help identify risk factors negatively influencing treatment outcomes.